PENGARUH BRAND IMAGE (CITRA MEREK), KEPRIBADIAN DAN PROMOSI TERHADAP KEPUTUSAN PENDENGAR MEMILIH LEMBAGA PENYIARAN RADIO PERSADA 92,4 FM PEKANBARU - Wicara, Dinda Genta (Sekolah Tinggi Ilmu Ekonomi Riau, 2016)
The problem in this research was listener decision in choosing Persada Riau Broadcast 92,4 FM Pekanbaru. Research variables were brand image, personality, promotion and listener decision. The purpose of this research to show (1) The Influence Of Brand Image, Personality and Promotion simultaneously toward listener decision, (2) The Influence Of Brand Image, Personality and Promotion Partially toward listener decision. Based on observation and prliminary study,writer found that listener decision in choosing Persada Radio Broadcast 92,4 FM Pekanbaru. Is in low category.writer guested that thelow of listener decision because of severalfactors, which are, the low of company brand image by listener, the low of listener decision in choosing Persada Radio Broadcast, the promotion of broadcast Radio is not enough adequate. In sloving the problem, there were two hipothesis. First : There is an Influence of Brand Image, Personality and Promotion Broadcast 92,4 FM Pekanbaru. Second : There is an Influence of Brand Image, Personality and Promotion partially toward Listener Decision in Choosing Persada Radio Persada Broadcast 92,4 FM Pekanbaru.The Population was community of persada broadcast 92,4 FM Pekanbaru. The total number of population was 455 participant. Sampling in this research calculte by using slovin formula as many as 82 respondent. Data collection by using questionaire of likert scale. Then,the questionqires analyzed by using correltion technique and multiple linier regression in SPSS for windows version 19. The analysis finding shows that brand image, personality and promotion simultaneously toward listener decision got contribution score 58,7 %. The influence in regression Y= 14,422+0,496X1-0,381X2+0,513X3. According to research finding, writer concluded that there is significant influence or brand image, personality and prootion simultaneously toward listener decision. Writer suggested to company to increase their brand image tolistener. And understanding listener personality with appropriate program, then increasing promotion. It did not mean that others unresearch factors were ignored